Remote sensing of inland Sabkha and a study of the salinity and temporal stability for sustainable development: A case study from the West coast of Qatar - Sankaran Rajendran (14152830) (2021)
The inland sabkha of the Arabian Gulf is important to study for the occurrence of minerals, rocks, soil salinity, and stability of the sabkha due to the high demand for infrastructure and agriculture development region. This study describes the spectral absorptions of evaporite minerals, discriminates rocks, maps salt crusts, gypsiferous soil flats, and soil salinity, and studies the temporal stability of an inland sabkha of the Dukhan area, west coast of the State of Qatar. This was performed using satellite data of the Hyperion of EO1, ASTER of Terra, and multispectral instrument (MSI) of Sentinel-2. The occurrence of minerals in the area is detected using Hyperion data by the linear spectral unmixing (LSU) method and studied for their spatial distribution. The different geological formations of the sabkha were discriminated by using the VNIR (visible and near-infrared) and SWIR (shortwave infrared) spectral bands from ASTER by principal component analysis (PCA). The image developed by using the principal components (R:PC2, G:PC3, B:PC5) showed the formations in different tones. Salinity of the area was mapped using monthly data of MSI from 2018 to 2020 by normalized difference salinity index (NDSI) (band11-band12)/(band11 + band12). The results of the index displayed the distribution of salinity in the area. Besides, moisture of the area was studied by using the normalized difference moisture index (NDMI) (b8-b11)/(b8 + b11) and described the temporal stability of the sabkha. All the results of image analyses were validated through field and laboratory studies. The study of laboratory spectra of evaporite minerals namely gypsum, anhydrite, and halite present in the salt crusts and gypsiferous soil flats showed their unique spectral absorptions in between 1.4–1.5 μm and 1.9–2.0 μm whereas, the calcite and dolomite minerals of the carbonate formations exhibited deep absorptions near 2.345 and 2.495 μm respectively. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2021.146932